Citizenship Education Development: European Experience - A. V. Suslov (Образование и наука)
The paper considers the European experience of the citizenship education developmentan important aspect of internal policy in the most countries. The education in question is considered to be the democratic citizenship training aimed at developing the loyal attitude to different value priorities in society, social responsibility, active citizenship position, awareness of democratic rights, capability of using and protecting them.The author looks at the transformation of citizenship education concept in the last three decades from the civics education (i.e. history, political science, law, etc.) to the democratic citizen education. The paper analyzes differ- ent approaches to citizenship education in several European countries including the post-soviet ones. It is emphasized that both in western and eastern Europe a lot of effort is made for spreading and supporting the education in question. The author recommends considering the foreign experience of integrating the democratic citizenship education into the state academic curricula at the primary, secondary and higher school levels.